Pendampingan Strategi Marketing Berbasis Digital pada Kelompok Usaha Perajin Tapis dan Batik di Kabupaten Pringsewu Lampung - Hilda Dwi Yunita; Fatimah Fahurian; Yodhi Yuniarthe; Triyugo Winarko; Hamdan Sukri (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2025)
Pringsewu Regency is one of the regencies in Lampung Province that has a creative economy. There are many business groups there, almost all of whom sell their craft products or superior products such as bamboo weaving, tapis crafts, batik crafts, clay crafts, snack businesses, brick and tile industries. However, the marketing or sales process is still carried out conventionally, namely sales can only be done within the region due to the limited promotional or marketing area. Less than optimal marketing of a product can result in high or low income or earnings for the business group or craftsman. All of this is due to the lack of media that can be used for online marketing. To address these issues, the PKM team of the Faculty of Computer Science, Mitra Indonesia University, utilized technology to conduct mentoring and training activities on Digital-Based Marketing Strategies. Furthermore, these training and mentoring activities were conducted through several sessions, so that participants had sufficient time to understand the technology and develop skills in using innovative technology products. The results of this community service activity are expected to inspire participants on how to market products more creatively using technology media so as to increase sales access and access to higher income for micro-businesses in general and especially for micro-businesses of Tapis and Batik artisans in Pringsewu Regency, Lampung.